Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Mega Finance Cabang Palembang - Muhammad Deri Sagitario; Riri Hanifa; Rikkie Dekas (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
Employee performance is the result of work in terms of quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Real behavior displayed by eah person as work performance produced by employees according to their role in a company or organization. Good employee performance is one of tthe most important factors in a company or organization’s efforts to increase productivity. The purpose of this research is to determine the influence of Compensation and Work Environment on Employee Performance. The number of samples in this study was 61 respondents using probbility sampling techniques. The analysis tchnique used is multiple linear regression analysis, t test and F test. The results of this research show that compensation has a positive and significant effect on employee performance. The work environment has a positive and significant effect on employee performance.